Cracking rare disorders: a new minimally invasive RNA-seq protocol - Laurenz De Cock; Erika D’haenens; Lies Vantomme; Lynn Backers; Aude Beyens; Kathleen BM Claes; Griet De Clercq; Robin de Putter; Candy Kumps; Nika Schuermans; Jo Sourbron; Hannes Syryn; et al. (npj Genomic Medicine)
Abstract RNA sequencing (RNA-seq) has become key to complementing exome and genome sequencing for variant interpretation. We present a minimally invasive RNA-seq protocol using short-term cultured peripheral blood mononuclear cells (PBMCs) with and without cycloheximide treatment, enabling detection of transcripts subject to nonsense-mediated decay. While broadly applicable, this protocol is particularly suited for neurodevelopmental disorders, as up to 80% of the genes in our intellectual disability and epilepsy gene panel are expressed in PBMCs. Applied to 46 affected individuals and 15 parents, RNA-seq revealed splicing defects in six of nine individuals with splice variants, allowing reclassification of seven variants. Targeted cDNA analysis confirmed aberrant splicing in four individuals but missed intron retention in two. Global analyses (FRASER, OUTRIDER, and monoallelic expression) supported findings but did not yield new diagnoses. We propose a flowchart integrating RNA-seq into diagnostic workflows. Overall, our protocol is easily implementable, captures complex splicing events, and enhances variant classification.